Foreign language as a means of professionally oriented technical education (Eurasian Journal of Philology Science and Education, 2016)
In this article it is noted that the paradigm of a foreign language as a target acquisition becomes a means of achieving professional competence. The education system in our country is systematically reformed – requirements for learning outcomes change, training programs improve, the experience of foreign universities is adopted; there is also a convergence of domestic and foreign universities according to the Bologna Process. There are also activities for the development and improvement of the state educational standards of higher education in the competency format, the definition and classification of competencies, as well as their content are clarified. All of the above processes in education are a reaction to the phenomenon of globalization in the economy and labor market.
Keywords: language competences; professionally oriented foreign language; peculiarities of language learning of non language specialties; academic mobility for engineering students; linguistic features; cultural lin¬guistics; language abilities